ANALISIS KINERJA BIAYA DAN WAKTU PADA PROYEK PEMBANGUNAN JALAN AKSES BUMI PERKEMAHAN GANDUS DENGAN METODE EARNED VALUE - Septriansyah, Verinazul; Umari, Zuul Fitriana; Wartini, Wartini; Akhirini, Akhirini; Anugerah, Rizki (Program Studi Teknik Sipil, Fakultas Teknik, Universitas Tridinanti, 2024)
The Gandus Camping Ground Access Road Construction Project is required to be completed on time so that consumer confidence is maintained. To achieve this, control is needed which must be known in advance through ongoing project performance. One way to determine project performance is the Earned Value method which integrates aspects of cost, time and work performance. Therefore, this Earned Value analysis is applied to the Gandus Campground Access Road Construction Project. Project performance is analyzed based on cost performance index (Cost Performance Index) and time (Schedule Performance Index). Calculations are based on planned value, earned value and actual costs. Performance control is reviewed for 8 weeks, namely week 12 to week 19. The results of the analysis in weeks 12 to 19 show that the costs incurred were greater than planned and the implementation time was longer than planned as indicated by the average value of CPI = 0.976 (CPI <1) and the average value of SPI = 0.999 (<1). The results of the estimated final project cost are IDR 3,740,377,358.49 with an implementation time of 24 weeks, which means the project will be in accordance with plan.